Development artificial dental filling (PMMA) for antibacterial and wear resistance enhanced by bioceramic system CaTiO3 - Fadhil K. Farhan; Zainab Al-Ramadhan; Ali Hadi Hassan Al-Batat (Al-Qadisiyah Journal of Pure Science, 2018)
In this paper, bioactive ceramics of calcium oxides prepared from egg shells and nano-titanium dioxide were used in a 1: 1 ratio and were mixed with a polymeric bonding material suitable for medical applications. Dry mixing and homogenous mixing were used. Ultrasonic technology was then used to prepare the nanoparticles that were then formed in standard dimensions for the purpose of conducting the required tests. The screw technique was used on the disk to calculate the rate of wear and tear, weight and volume, as well as the wear and tear coefficient. The concrete hardness scale was used to calculate the scratch resistance of the surface. The results of the various types of wear and tear index were significantly improved by the successive additions of ceramic material (calcium tetanite) as well as by increasing the scratch resistance of the prepared models obtained from the hardness scale. Synthetic tests (electronic scanning microscopy and x-ray diffraction) were used to interpret the results as well as to examine the material prepared against the bacteria.